PENGARUH LATIHAN REACTIVE AGILITY DAN CONE DRILL TERHADAP KEMAMPUAN DRIBBLING PEMAIN SEKOLAH SEPAK BOLA PUTRA BUMI SERAMBI U-14 - Dedek Kurniawan; Padli; Roma Irawan; Vega Soniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of Reactive Agility and Cone Drill training on dribbling ability among U-14 players of Putra Bumi Serambi Soccer School. This study used a quasi-experimental method with a Two Group Pretest-Posttest Design. The sample consisted of 20 players divided into two treatment groups, namely Reactive Agility and Cone Drill groups. The instrument used was the Zig-Zag Dribbling Test. Data were analyzed using normality tests, homogeneity tests, Paired Sample t-test, and Independent Sample t-test at a significance level of 0.05. The results showed that Reactive Agility training improved dribbling ability by 6.06%, while Cone Drill training improved dribbling ability by 4.67%. The paired sample t-test indicated that both training methods significantly improved dribbling ability (p<0.05). However, the independent sample t-test showed no significant difference between the two methods (Sig.=0.058>0.05). Therefore, both Reactive Agility and Cone Drill training are effective methods for improving dribbling ability among U-14 soccer players. Football players should gradually integrate Reactive Agility and Cone Drill training into youth development programs to improve players' dribbling skills. Future research is recommended using a larger sample size, longer training duration, and combining both training methods to obtain a more comprehensive picture of effectiveness.